Breeding capacity - Labrada, Humberto Reos (Technical Centre for Agricultural and Rural Cooperation, 2002)
Historically, plant breeding has followed two independent, parallel tracks a formal, scientific one and one followed by farmers. Tuning scientific research and formal breeding programmes to farmers knowledge and selection criteria is an...